1982
DOI: 10.1130/mem156-p203
|View full text |Cite
|
Sign up to set email alerts
|

10: Gravity and magnetic anomaly studies of Lake Superior

Abstract: Gravity and magnetic anomalies in Lake Superior are useful in tracing out the subsurface extent and geometry of igneous rocks of the Keweenawan Supergroup that crop out around the lake and on islands within the lake. The data show that the Lake Superior structural basin generally is outlined by the shoreline of the lake. The limbs of the elongated basin are delineated by gravity and magnetic maxima that occur over outcropping and buried mafic volcanic rock. The basin anomalies at the southwestern and southeast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

1985
1985
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(15 citation statements)
references
References 6 publications
2
13
0
Order By: Relevance
“…Receiver function stud-ies have not been done in the MCR but earlier geophysical investigations in MCR by Cannon et al 4 have indicated a crustal thickening beneath the rift of about 45 km, assumed to be caused by the presence of magmatic underplating above a modified lower crust, 5 or a basaltic dome in the lower crust causing flexure of the upper crustal layers. 6 Seismic studies by Hinze et al, 7 Behrendt et al 8 indicated a more complex crust consisting of low velocity sedimentary rocks overlying a thick section of mafic volcanic rocks. The Consortium for Continental Reflection Profiling (CORCORP) deep seismic profiling in the 1970s across both limbs showed fault bounded basins of volcanic rocks overlain by thick clastic sedimentary rock units.…”
Section: Introductionmentioning
confidence: 98%
“…Receiver function stud-ies have not been done in the MCR but earlier geophysical investigations in MCR by Cannon et al 4 have indicated a crustal thickening beneath the rift of about 45 km, assumed to be caused by the presence of magmatic underplating above a modified lower crust, 5 or a basaltic dome in the lower crust causing flexure of the upper crustal layers. 6 Seismic studies by Hinze et al, 7 Behrendt et al 8 indicated a more complex crust consisting of low velocity sedimentary rocks overlying a thick section of mafic volcanic rocks. The Consortium for Continental Reflection Profiling (CORCORP) deep seismic profiling in the 1970s across both limbs showed fault bounded basins of volcanic rocks overlain by thick clastic sedimentary rock units.…”
Section: Introductionmentioning
confidence: 98%
“…3). These intense anomalies are not well understood, although Hinze et al (1982) and Dickas (1986c) suggest that they might be produced by relatively thick sections of low-density Bayfield Group sedimentary rocks, thinning of the rift's dense volcanic sequence, or low-density sources beneath the rift basin. White (1966b) suggested that the southern (Bayfield Peninsula) negative anomaly is produced by a ridge of pre-Keweenawan basement rocks above which the rift's volcanic rocks are relatively thin or absent.…”
Section: Geophysical Elements and Methodologymentioning
confidence: 96%
“…The transitional zone between supratidal and subtidal mudstones defines the potential Richfield carbonate reservoir fairway. (Hinze et al, 1982).…”
Section: Bouguer Gravity Relationships To Facies Depositionmentioning
confidence: 99%